Returning Home - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2003)
"Returning Home" by Anthony Trollope is a novel that falls within the Victorian era, capturing themes of nostalgia and the longing for home against the backdrop of the writer's contemporary society. This poignant tale revolves around the experiences of a couple, Mr. and Mrs. Arkwright, as they undertake a challenging journey to return to England after years of living abroad in Costa Rica. The narrative explores the contrasts between the excitement associated with foreign adventures and the deep-seated yearning for the comforts and familiarity of home. The story follows the Arkwrights as they prepare for their arduous journey back to England, igniting Mrs. Arkwright's hopes of reuniting with her family after four long years. Their initial excitement quickly turns into dread as they encounter the harsh realities of travel through the treacherous rainforests. Despite arduous challenges, including exhausting travel conditions and extreme weather, the couple remains determined. However, tragedy strikes during their river voyage when a mishap leads to the drowning of Mrs. Arkwright, a moment that shatters their dreams of homecoming and leaves Mr. Arkwright to grapple with profound grief and guilt. Through this tale, Trollope examines the fragility of human aspirations and the bittersweet nature of returning home. (This is an automatically generated summary.)
Release date is 2003-02-01
Transcribed from the 1864 Chapman and Hall (3z(BTales of All Countries(3y (Bedition by David Prices
Keywords: Short stories; Travel -- Fiction; British -- Costa Rica -- Fiction